Gaining more insight into the determinants of candida species pathogenicity in the oral cavity - Arzmi, Mohd Hafiz; E., Alshwaimi; Wan Harun, Wan Himratul Aznita; Abdul Razak, Fathilah; Michael, McCullough; Nicola, Cirillo (Sage, 2014)
Candida infection (candidiasis) is potentially life threatening and can occur in almost all anatomical sites, including the mouth. Candida species are in fact the most common fungal pathogens isolated from the oral cavity and frequently cause superficial infections such as oral candidiasis and denture-associated erythematous stomatitis. Whilst systemic dissemination of Candida from intraoral foci is rare and largely due to severe deficits of the host immune defenses, the development of localized oral candidiasis is most commonly related to a variety of non-immune determinants such as Candida virulence factors and permissive oral microenvironment. In particular, phenotypic switching and dental biofilm have emerged as major determinants for the pathogenicity of Candida and are currently the subject ofintense research. An understanding of the molecular aspects underlying the biological behavior of Candida will be the key to the development of effective preventive as well as therapeutic measures for invasive and oral candidiasis.